The Scholarly Impact of Student Authorship in Ophthalmology - Prasad, Minali; Paracha, Munizay; Goodman, Deniz; Cabral, Howard J.; Christiansen, Stephen P.; Subramanian, Manju L. (Journal of Academic Ophthalmology, 2023)
Purpose The H-index (Hi), an author-level metric of scholarly impact, is predictive of future scientific achievement. We sought to analyze the scholarly impact of student authorship on the Hi of corresponding authors (CAs) within a major academic journal in the specialty of ophthalmology.Materials and Methods We compared the Hi of all unique CAs for manuscripts published in Ophthalmology (Journal of the American Academy of Ophthalmology) in 2008, 2012, and 2016. Data abstraction was completed twice: in October 2018 and March 2021. We further grouped published articles for CAs into those with student authors (StA) and those without (nStA). Primary analysis involved a linear regression analysis with change in Hi from October 2018 to March 2021 as the outcome variable, CA groups as the predictor variable, adjusting for the covariates of baseline Hi, the year when the CA published his or her article, number of research items published in October 2018, and the academic appointment of the CAs. Secondary analysis involved a linear regression analysis with change in Hi from October 2018 to March 2021 as the outcome variable, total number of student authors per CA as the predictor variable, adjusting for the covariates of baseline Hi, the year CA published his or her article, number of research items published in October 2018, and the academic appointment of the CAs.Results The number of student authors increased from 168 in 2008 to 192 in 2016. Of the 902 articles, 316 articles were co-authored by one or more student authors. The average change in Hi of CAs publishing with student authors (StA, 11.0 ± 14.7) was significantly greater (p < 0.0001) than the change in Hi of CAs publishing without student authors (nStA, 6.2 ± 6.2). As the total number of student authors increased, the change in Hi of CAs increased linearly for all years combined (regression coefficient = 1.70, p-value < 0.0001).Conclusion CAs publishing with students in the field of ophthalmology have a higher scholarly impact than those publishing without students. The development of programs to integrate students into ophthalmology research early on may encourage their pursuit of a career in ophthalmology, while advancing the careers of their mentors.
Keywords: H-index; student author; mentor; ophthalmology